Tourism and Transformation: Changing Livelihood Practices of Mountain Dwellers (Journal of Tourism and Himalayan Adventures, 2020)
This article is about major changes in the lives of mountain dwellers brought by tourism. The article focuses on the people of the Khumbu region in general and the Lukla bazar in particular. Based on the primary research, the article reveals changing livelihood practices of both the Sherpa and the non-Sherpa people. The article mainly focuses on how traditionally agro-pastoralist Sherpa people transformed their everyday lives into multiple occupations. Tourism development has also supported the in-migration of non-Sherpa people and the out-migration of the Sherpa that not only made both groups dependent on tourism sectors but also ended the Sherpa’s monopoly on tourism businesses.